2020
DOI: 10.3390/met10091258
|View full text |Cite
|
Sign up to set email alerts
|

The Pitting Corrosion Behavior of the Austenitic Stainless Steel 308L-316L Welded Joint

Abstract: The pitting corrosion resistance of the austenitic stainless steel 308L-316L welded joint was investigated by electrochemical tests. It is found that the weld zone was the most critical for pits to initiate in the welded joint due to relatively instable passive film with few Mo and inhomogeneous passive film induced by multiple (Mn, Al, and Si) oxides and continuous network of 13.94 vol.% δ ferrites. By statistical analysis, 53.8% pits initiated at (Mn, Al, and Si) oxides, 23.0% in austenite, and 23.2% at inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Pitting corrosion is the primary type of corrosion of stainless‐steel joints and is mainly ascribed to the appearance of an unstable, nonuniform passivation film. [ 29–31 ] The pitting nucleates grow and spread in all directions or into the metal, thereby accelerating the corrosion process. For the laser‐arc hybrid welding of high‐nitrogen steel, the additional nitrogen in the wire or protective gas can optimize the surface passive film's composition, improving the pitting resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Pitting corrosion is the primary type of corrosion of stainless‐steel joints and is mainly ascribed to the appearance of an unstable, nonuniform passivation film. [ 29–31 ] The pitting nucleates grow and spread in all directions or into the metal, thereby accelerating the corrosion process. For the laser‐arc hybrid welding of high‐nitrogen steel, the additional nitrogen in the wire or protective gas can optimize the surface passive film's composition, improving the pitting resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Recent literature suggested that the complex microstructure produced during welding results in preferential corrosion in the weld metal at alloy-depleted regions or δ/γ interfaces that leads to failure of components in several industries. [10][11][12][13] The presence of nitrogen even in minor amounts can affect the properties of SSs. The beneficial effect of nitrogen alloying in SS is a remarkable increase in strength and toughness, and excellent corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6–9 ] Recent literature suggested that the complex microstructure produced during welding results in preferential corrosion in the weld metal at alloy‐depleted regions or δ/γ interfaces that leads to failure of components in several industries. [ 10–13 ]…”
Section: Introductionmentioning
confidence: 99%